A multichannel relay MAC protocol for IEEE 802.11 wireless LANs. (19th March 2013) - Kim, Dong‐Wook; Lim, Wan‐Seon; Suh, Young‐Joo
SUMMARY One of the challenging issues in wireless LANs (WLANs) is improving the network throughput. One of the possible solutions for the issue is maximizing the number of concurrent transmissions. Although some protocols have been proposed to exploit transmission concurrency in WLANs, their performance depends on the degree of the interference among links. Also, it is hard to obtain interference information because of their dynamics. In this paper, we propose an enhanced medium access control (MAC) protocol for WLANs, named multichannel relay MAC (MRMAC), which is able to transmit multiple frames simultaneously without considering interference. To enable concurrent transmissions, MRMAC adopts the concept of frame relaying. Furthermore, MRMAC utilizes several nonoverlapping channels to eliminate interferences. Through extensive simulations, we found that MRMAC shows better performance than existing well‐known MAC protocols. Copyright © 2013 John Wiley & Sons, Ltd.